Decentralized computation method for robust operation of multi-area joint regional-district integrated energy systems with uncertain wind power. (15th September 2021) - Gan, Wei; Yan, Mingyu; Yao, Wei; Guo, Jianbo; Ai, Xiaomeng; Fang, Jiakun; Wen, Jinyu
Highlights: The multi-area integrated energy system is constructed for enhanced flexibility. Robust optimization is applied to accommodate uncertainties of wind power. A tri-level algorithm is designed to solve robust multi-area problem distributedly. Three simulation systems are conducted to validate the model and its algorithm. Abstract: Large-scale integrated energy systems often encompass several subsystems divided by geographic areas. Coordinated operation of multi-area integrated energy systems can enhance operational flexibility, which is crucial for systems with high wind power penetration. Traditional centralized methods have some inherent defects, such as privacy protection, communication burden, and computational capability, etc. To address such challenges, this paper proposes a decentralized computation method for the robust operation of multi-area joint regional-district integrated energy systems with uncertain wind power. The interconnected multiple areas can cooperate for improved system flexibility and wind power integration capability. Using the decentralized method, the area operator optimizes its operation decisions independently without transferring its dispatch rights. The shared information is limited to exchanged energy flows. The proprietary information is thus preserved while the communication burden is significantly reduced. To solve the robust operation problem distributedly, the decentralized method is enhanced to cope with both deterministic and robust problems. A tri-level algorithm composed of the iterative alternating direction multiplier method and the column constraints generation method is utilized to realize the decentralized optimization. Numerical results for three test systems show the effectiveness, computational quality, and scalability of the proposed method. Compared to the isolated method, the proposed method fully utilizes the coordination effect of multi-area RD-IES and has obvious economic advantages, especially in scenarios with high wind power penetration levels. The proposed method brings a 12.4% cost reduction in the two-area system and a 22.4% cost reduction in the eight-area system.